2022
DOI: 10.1186/s12954-022-00708-3
|View full text |Cite
|
Sign up to set email alerts
|

Music festival drug checking: evaluation of an Australian pilot program

Abstract: Background This paper explores the feasibility of delivering a music festival-based drug checking service in Australia, evaluating service design and stakeholder acceptability. Methods Questionnaire and interview data were collected from adult service users and key stakeholders. A mixed methods approach was used to analyse the data on implementation, impact and acceptability. Results The trial service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Just over half of the present sample reported changing their drug taking behaviour because of KYSNZ service use, with the majority of clients learning a moderate to large amount about harm reduction through their use of KYSNZ. These data are similar to that reported internationally [ 49 – 51 ], and within Aotearoa [ 27 ], highlighting the positive influence that drug checking services can have on the knowledge and behaviour of people who use drugs. Furthermore, the majority of those who did not indicate behaviour change reported that they believed their drug taking behaviour was safe, indicating that lack of change was not due to a failure of KYSNZ to have positive influence over “unsafe” client behaviour.…”
Section: Discussionsupporting
confidence: 88%
“…Just over half of the present sample reported changing their drug taking behaviour because of KYSNZ service use, with the majority of clients learning a moderate to large amount about harm reduction through their use of KYSNZ. These data are similar to that reported internationally [ 49 – 51 ], and within Aotearoa [ 27 ], highlighting the positive influence that drug checking services can have on the knowledge and behaviour of people who use drugs. Furthermore, the majority of those who did not indicate behaviour change reported that they believed their drug taking behaviour was safe, indicating that lack of change was not due to a failure of KYSNZ to have positive influence over “unsafe” client behaviour.…”
Section: Discussionsupporting
confidence: 88%
“…Following counselling after receiving the results of the chemical analysis, 42% of participants intended to change their behaviour based on the medical and counselling advice they received at the service, demonstrating that the service had the potential to affect behaviour [ 27 ]. This was later confirmed by the evaluation of the 2019 service [ 36 , 37 ].…”
Section: Step 8: Generating Short-term Winsmentioning
confidence: 79%
“…Utilizing reagent testing kits was another widely adopted strategy for seeking information on the content and purity of drugs sourced as MDMA, with findings suggesting that people who use drugs would be receptive to health advice from a peer workforce delivered in a culturally safe setting, such as Australia's DanceWize programs, and the CanTEST fixed-site drug checking pilot in the ACT (CAHMA, 2022; Duff et al, 2007). Moreover, existing literature on drug checking pilots at Australia's Groovin the Moo festival in the ACT have indicated that people will discard their “MDMA” at the advice of health professionals when there is an indication that the substance may be dangerous (Makkai et al, 2018; Olsen et al, 2019; Vumbaca et al, 2019).…”
Section: Discussionmentioning
confidence: 99%